Retrospective analysis of efficacy, safety, and prognostic factors in a cohort of Chinese hepatocellular carcinoma patients treated with drug-eluting bead transarterial chemoembolization - Chen,Sihan (2019)
The aim of our study was to assess the efficacy, safety, and prognostic factors of drug-eluting bead transarterial chemoembolization (DEB-TACE) in Chinese hepatocellular carcinoma (HCC) patients. Patients (n=102) diagnosed as primary HCC were consecutively enrolled in this retrospective cohort study. Treatment responses were assessed following the modified Response Evaluation Criteria in Solid Tumors. Progression-free survival (PFS) and overall survival (OS) were evaluated, and adverse events (AEs) as well as liver function-related laboratory indexes of all DEB-TACE records (N=131) were assessed. Complete response (CR) rate, objective response rate, and disease control rate were 51.0, 87.3, and 95.1%, respectively, at 1–3 months post DEB-TACE. The mean PFS and OS were 227 (95%CI: 200–255) days and 343 (95%CI: 309–377) days, respectively. Multivariate logistic regression revealed that portal vein invasion and abnormal total protein (TP) were independent predictive factors for worse CR, and multivariate Cox's regression analysis showed that multifocal disease independently correlated with shorter PFS. Most of the liver function-related laboratory indexes worsened at 1 week but recovered at 1–3 months post-treatment, only the percentage of patients with abnormal ALP increased at 1–3 months. In addition, 112 (85.5%), 84 (64.1%), 53 (40.5%), 40 (30.5%), and 16 (12.2%) patients had pain, fever, nausea, vomiting, and other AEs, respectively. DEB-TACE is efficient and safe in Chinese HCC patients, and portal vein invasion, abnormal TP level as well as multifocal disease could be used as unfavorable prognostic factors to DEB-TACE treatment.